Pemimpin yang Baik Dalam Organisasi : Pelatihan Kepemimpinan (LDKM 2023) Dari Psychological View - Alfaiz, Alfaiz; Julius, Andre; Tahir, Muthahharah; Rachmaniar, Ananda (Fakultas Ushuluddin, Adab, dan Dakwah, 2024)
This article was prepared to share insights, perspectives and knowledge through lectures and training for prospective young leaders in organizations, within the framework of Basic Student Leadership Training (LKDM) activities. In the 2023 LDKM setting, students consist of various study programs who will be appointed as candidates to become administrators of HIMA Study Programs and Faculties at Ma'soem University. The material is given in the form of presentations with tutorials to discussions and implementation in cases of leadership within campus organizations. As a result of this service, participants from LDKM 2023 activities gain new insight and knowledge so that in the process they will personalize this in organizational activities and even in their daily lives.